Hypokalemic thyrotoxic periodic paralysis in a young Serbian male - Ristić Petar; Dragović Tamara; Kiković Saša; Ristić Dragana; Zdravković Marija; Hinić Saša; Durmić Tijana; Hajduković Zoran (Vojnosanitetski Pregled)
Introduction. Hypokalemic thyrotoxic paralysis is a very rare form of periodic paralysis in Caucasian population. In this population, a more frequent form is familiar hypokalemic periodic paralysis with the same clinical presentation. It is flaccid paralysis of proximal muscles in extremities. Having in mind that clinical presentation of hyperthyroidism in these patients is milder than it could be expected with given values of thyroid hormones, differential diagnosis to other forms of hypokalemic paralysis is essential. Case report. We presented a case of a young male with hyperthyroidism and severe periodic flaccid paralysis particularly of leg muscles. Laboratory findings showed elevated thyroid hormones levels and hypokalemia during the attacks with normalized potassium levels between attacks. The patient had no relatives with the similar condition. Also, he never had anything like these attacks prior to development of hyperthyroidism. After differential diagnosis, other reasons for hypokalemic periodic paralysis were excluded. We intensified the hyperthyroidism treatment and resolved hypokalemic periodic paralysis attacks with potassium chloride (KCl) infusions. The patient was advised to start a definitive treatment of hyperthyroidism after stabilization of hormonal levels. Conclusion. Hypokalemic thyrotoxic paralysis is a rare and potentially dangerous condition which, if recognized, can be prevented by resolving hyperthyroxinemia and the use of nonselective β blockers.